MAKNA KERJA PERSPEKTIF EKONOMI ISLAM - Qomar, Moh Nurul (Irtifaq, 2014)
This study aims to link among religion and economics in the establishment a work ethic. Original thesis concerning relation among religion and work ethic made by Max Weber in his study entitled Protestant Ethic and the Spirit of Capitalism In Weberian perspective, as a basis for the theory to be developed in the Islamic economy. The method used in this research is to study literature. The findings in this study is the work ethic for a Muslim is worth worship gods command and not just wealth.Keywords : Work Ethic, Religious, Islamic Economics